Student Perceptions On The Use Of Youtube In Increasing Vocabulary - Muhammad Ari Saputra (Lembaga Pengembangan Kinerja Dosen, 2022)
This research is entitled “Students' Perception On the Use of YouTube to Develop Their Vocabulary”. The objective of the research is to identify, classify and describe the ways English Students use YouTube to develop their Vocabulary. It is also to analyze and describe students' perception on using YouTube to develop their vocabulary. This research used descriptive quantitative method. The research collected the data using questionnaires and interviews. The sample was 30 students' from the 2022 batch of English Department Faculty of Humanities. Thirty students' responses were collected by online questionnaire with google-form and answers collected by online interview with Whatsapp. The collected data were quantitatively analyzed by percentage formula. Using theory Freeman and Anderson (2011: 250) and to analyze the university students' perception about the use of YouTube to develop their vocabulary base on the theory of Nelson-Smith (2008:32). The results showed that most of the respondents had positive responses about the use of YouTube to develop their vocabulary. Since YouTube can be used both as providing teaching resources and enhancing learning experience. Based on the findings, it can be concluded that University students have positive perceptions on the use of YouTube in the use of media YouTube is considered useful to students, English Department, Sam Ratulangi University Since YouTube can be used both as providing teaching resources and enhancing learning experience. Based on the findings, it can be concluded that University students have positive perceptions on the use of YouTube in the use of media YouTube is considered useful to students at Sekolah Tinggi Agama Islam Negeri Mandailing Natal .